Solid state physics essential concepts - Snoke, David W. (Cambridge University Press, 2020)
This book centers on essential theoretical concepts in all types of solid state physics, using examples from speci c systems with real units and numbers. Each chapter focuses on a di erent set of theoretical tools. \Solid state" physics is particularly intended here, because \condensed matter" physics includes liquids and gases, and this book does not include in-depth discussions of of those states. These are covered amply, for example, in Chaikin and Lubensky.1 Researchers in the eld seem to be split in regard to the importance of the advanced topics of group theory and many-body theory. Some solid state physicists say that all of solid state physics starts with group theory, while others dismiss it 1 P.M. Chaikin and T.C. Lubensky, Principles of Condensed Matter Physics, (Cambridge University Press, 2000)"-- Provided by publisher.